KONSEP I’RAB DALAM ILMU NAHWU (Sebuah Kajian Epistemologis) (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2015)
Nahwu's knowledge as we know it today is ladenwith various rules and theories is the result of a processwhich is quite long in the history of Arabic linguistics. Wrong reviewNahwu science for example about the concept of I'rab. In things that are often frequentconsidered as a privilege that makes it difficult then to tryto be avoided by various methods recommended in Ta'līmal-Lughah al-abiArabiyah lī Ghair an-Nāthiqīn bihā, then actually thatis the completion of manipulation. That problem will always appear duringthe core of the problem has not been resolved completely. The concept of Iabrmust be straightened out. I've always defined it as taghyîr(change) or taghayyur (change) or atsar (address symptomsIhab).